1994
DOI: 10.1029/94jb01336
|View full text |Cite
|
Sign up to set email alerts
|

Curie point depth in northeast Japan and its correlation with regional thermal structure and seismicity

Abstract: Heat flow measurements are high on the back arc side and low on the forearc side of the Tohoku arc, but convective heat transfer in volcanic areas affects the heat flow measurements, complicating the determination of the thermal structure from heat flow measurements alone. Curie point depths deduced from previous magnetic analyses show a sudden change of the Curie isotherm between the volcanic front and the Japan Trench. A magnetic belt extends from west Hokkaido to the eastern limit of Tohoku. The location is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(53 citation statements)
references
References 33 publications
1
47
0
2
Order By: Relevance
“…To quantify the error in the estimated CPD, we evaluated the standard and statistical errors of the power density spectrum from the linear fit using the definition of the error adopted from Trifonova et al (2009) and Okubo and Matsunaga (1994). The results of the spectral analysis of aeromagnetic anomalies over the Ikogosi Warm Spring area show Curie point depth minimum estimates range between 11.5 ± 1.6 and maximum estimates 21.9 ± 1.7 km (Table 1) with an average value of 15.1 ± 0.6 km.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To quantify the error in the estimated CPD, we evaluated the standard and statistical errors of the power density spectrum from the linear fit using the definition of the error adopted from Trifonova et al (2009) and Okubo and Matsunaga (1994). The results of the spectral analysis of aeromagnetic anomalies over the Ikogosi Warm Spring area show Curie point depth minimum estimates range between 11.5 ± 1.6 and maximum estimates 21.9 ± 1.7 km (Table 1) with an average value of 15.1 ± 0.6 km.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, investigations have been made for parts of the territory of Japan (by Okubo 1985Okubo , 1989Okubo , 1994, USA (by Mayhew 1985;Blakely 1988), Greece (Tsokas et al 1998;Stampolidis and Tsokas 2002), Portugal (Okubo et al 2003), Bulgaria (Trifonova et al 2006(Trifonova et al , 2009 and Turkey (Dolmaz et al 2005;Maden 2009). Authors consider the power spectrum of the total geomagnetic field intensity anomaly over a single rectangular block using the expression, which was first given by Bhattacharyya (1965).…”
Section: Spectral Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…One of the methods for examining the thermal structure of the crust is the estimation of the CPD using aeromagnetic data (Smith et al, 1977;Okubo et al, 1985Okubo et al, , 1989Okubo et al, , 1994Okubo et al, , 2003Tsokas et al, 1998;Tanaka et al, 1999;Stampolidis and Tsokas, 2002;Dolmaz et al, 2005;Ates et al, 2005;Aydin et al, 2005;Qingqing et al, 2008;Li et al, 2010;Li, 2011;Bilim, 2011;Manea and Manea, 2011;Abd El Nabi, 2012;Hisarli et al, 2012;Saleh et al, 2013;Sayed et al, 2013;Abraham et al, 2014;Obande et al, 2014;Starostenko et al, 2014). Various studies have shown correlations between Curie temperature depths and average crustal temperatures, leading to viable conclusions regarding lithospheric thermal conditions in a number of regions around the world (Ross et al, 2006;Rajaram, 2007;Bouligand et al, 2009).…”
Section: Centroid Depth Methods For Calculating Dbms 221 Random Magmentioning
confidence: 99%
“…In recent years, this approach is widely adopted for estimating Curie-isotherm depth of the crustal rocks (e.g. Hong et al, 1982;Okubo et al, 1994;Tanaka et al, 1999;Aydin et al, 2005;Ross et al, 2006;Aydin and Oksum, 2010). Abdeslem (1995) introduced a method for interpretation of gravity anomalies using prism model.…”
Section: Methodsmentioning
confidence: 99%